The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/mbo3.1192
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal mechanism of Bacillus amyloliquefaciens strain GKT04 against Fusarium wilt revealed using genomic and transcriptomic analyses

Abstract: The application of endophytic bacteria, particularly members of the genus Bacillus , offers a promising strategy for the biocontrol of plant fungal diseases, owing to their sustainability and ecological safety. Although multiple secondary metabolites that demonstrate antifungal capacity have been identified in diverse endophytic bacteria, the regulatory mechanisms of their biosynthesis remain largely unknown. To elucidate this, we sequenced the entire genome of Bacillus amylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…(termed induced systemic resistance, ISR) ( Lugtenberg and Kamilova, 2009 ; Chen et al, 2020 ). The metabolites of B. amyloliquefaciens can be used to control root, leaf, and post-harvest diseases of major cash crops, such as sugarcane, tobacco, and tomato ( Liu et al, 2020 ; Tian et al, 2021 ; Zhao, 2021 ). B. amyloliquefaciens can promote crop growth or inhibit pathogens by producing and secreting secondary metabolites ( Salazar et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…(termed induced systemic resistance, ISR) ( Lugtenberg and Kamilova, 2009 ; Chen et al, 2020 ). The metabolites of B. amyloliquefaciens can be used to control root, leaf, and post-harvest diseases of major cash crops, such as sugarcane, tobacco, and tomato ( Liu et al, 2020 ; Tian et al, 2021 ; Zhao, 2021 ). B. amyloliquefaciens can promote crop growth or inhibit pathogens by producing and secreting secondary metabolites ( Salazar et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids are indispensable components in the formation of cell structures and various enzymes. The degradation of valine, leucine and isoleucine might be related to propanoate metabolism, which enters the TCA cycle ( Tian et al, 2021 ). DEGs of valine, leucine and isoleucine degradation were all upregulated in this work, indicating that some cell structures and enzymatic activities might be damaged, similar to the hyphal morphological changes in P. amygdali .…”
Section: Discussionmentioning
confidence: 99%
“…Chitinase and glucanase were reported to be major mucolytic enzymes that dissolve fungal cell walls ( Ji et al, 2020b ). Lipopeptides such as iturins and surfactin from Bacillus are widely known for targeting the host cell wall that causes its collapse and the membrane through pore formation, ultimately leading to cell death and inhibiting fungal growth ( Someya, 2008 ; Tian et al, 2021 ). Wang et al (2014) identified a 55 kDa antifungal protein produced by the B. licheniformis HS10 strain that was a carboxypeptidase and had significant inhibitory effects on eight different plant pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…More than 20,000 distinct bioactive chemicals have been found in marine fauna and flora to date [34,35]. Previously, different species of Bacillus with confirmed biocontrol activity against Foc have been reported, including B. amyloliquefaciens GKT04 [36,37], W19 [38], NIN-6 [39], and NJN-6 [40], B. velezensis HN03 [41], and (iii) B. subtilis strains B26 [42], B04, B05 and B10 [43], and N11 [44]. However, an extensive screening of the biocontrol strains from marine bacteria to control FWB pathogen is limited.…”
Section: Discussionmentioning
confidence: 99%